Functional decline in hospitalized older patients with coronavirus disease 2019: a retrospective cohort study - Tomohiro Hosoda (BMC, 2021)
Abstract Background This study aimed to determine the frequency of functional decline and to identify the factors related to a greater risk of functional decline among hospitalized older patients with coronavirus disease 2019 (COVID-19). Methods We reviewed the medical records of patients aged over 65 years who were admitted to a tertiary care hospital for COVID-19 over 1 year from February 2020. We evaluated the proportion of functional decline, which was defined as a decrease in the Barthel Index score from before the onset of COVID-19 to discharge. Multivariable logistic regression analyses were performed to evaluate the associations between the demographic and clinical characteristics of patients at admission and a greater risk of functional decline. Two sensitivity analyses with different inclusion criteria were performed: one in patients without very severe functional decline before the onset of COVID-19 (i.e., limited to those with Barthel Index score ≥ 25), and the other with a composite outcome of functional decline and death at discharge. Results The study included 132 patients with COVID-19; of these, 72 (54.5%) developed functional decline. The severity of COVID-19 did not differ between patients with functional decline and those without (P = 0.698). Factors associated with a greater risk of functional decline included female sex (adjusted odds ratio [aOR], 3.14; 95% confidence interval [CI], 1.25 to 7.94), Barthel Index score < 100 before the onset of COVID-19 (aOR, 13.73; 95% CI, 3.29 to 57.25), and elevation of plasma D-dimer level on admission (aOR, 3.19; 95% CI, 1.12 to 9.07). The sensitivity analyses yielded similar results to those of the main analysis. Conclusions Over half of the older patients who recovered from COVID-19 developed functional decline at discharge from a tertiary care hospital in Japan. Baseline activities of daily living impairment, female sex, and elevated plasma D-dimer levels at admission were associated with a greater risk of functional decline.